PERBAIKAN TEKNIK PENEBANGAN UNTUK MINIMASI LIMBAH PEMBALAKAN DENGAN CARA PENURUNAN TINGGI MULUT TAKIK REBAH - Wesman Endom (Jurnal Penelitian Hasil Hutan, 1996)
Felling technique in logging operation affect both quantity and quality of logs produced. Improperfelling operation may damage the wood in various ways such as splitting, splintering, and breakage. It leaves more wood wastes in the forest. This study  was attempted to reduce wood wastes in felling operation by improving felling technique i.e. through reducing height of undercut.The results showed  that the  reduction  of  height of standarized undercut  by 30-60% can increase  the volume of  log  produced  around  1 %. Calculation of the new method was found that additional  cost is relatively   small  only  about Rp. 344,13/m3. Application of this improvement technique, however  need a conclusive marketing system.